Secure pairing with biometrics. (24th February 2009) - Buhan, Ileana; Boom, Bas; Doumen, Jeroen; Hartel, Pieter H.; , Raymond N.J. Veldhuis
Secure pairing enables two devices that share no prior context with each other to agree upon a security association, which they can use to protect their subsequent communication. Secure pairing offers guarantees of the association partner identity and it should be resistant to eavesdropping and to a man-in the middle attack. We propose the SAfE pairing system, a user friendly solution to this problem. Details are presented along with a discussion of the security features, experimental validation with two types of biometric data (face recognition and hand grip pressure pattern) and a usability analysis for face recognition biometric pairing.